Application Of The Treffinger Learning Method To Improve Mathematical Reasoning In IT Al Maksum Sunggal SMP Students T.P 2020/2021 - Eggy Monicasari; Ellis Mardiana Panggabean (UMSU, 2021)
This study aims to (1) describe that the Treffinger Model can increase the activities of SMP IT Al-MaksumSunggal T.P 2020/2021 students. (2) To describe that the Treffinger Model can improve the mathematical reasoning of SMP IT Al-Maksum Sunggal T.P 2020/2021 students. The research subjects were students of class VII-A SMP IT Al-Maksum Sunggal T.P 2020/2021, totaling 19 people. This research is a classroom action research (CAR) which is carried out in 3 cycles. Each cycle consists of planning, implementing actions, observing and reflecting. Data were collected through observation, tests of students' mathematical reasoning abilities and interviews during the learning process. From the results of data analysis, it is concluded (1) The application of the Treffinger model can increase the activity of students of SMP IT Al-MaksumSunggal T.P 2020/2021. (2) The application of the Treffinger model can improve the mathematical reasoning of SMP IT Al-MaksumSunggal T.P 2020/2021 students.